Health Expenditures and Health Outcomes in Kenya - Manda, Damiano Kulundu; Mugo, Mercy G.; Murunga, James (European Scientific Journal, ESJ, 2020)
Health inputs are critical in attaining a healthy nation and improving health outcomes. Kenya, like other developing countries, grapples with limited health expenditures and poor population health indicators. Specifically, Kenya is yet to achieve the allocation of least 15% of the government’s annual budget to improve the health sector as enshrined in the Abuja Declaration. Though there is an improvement with regards to infant mortality rate decreasing from 96.6 per 1, 000 live birth in 1970 to 30.6 per 1, 000 live birth in 2018. This indicator of population health outcome is currently far below the Sustainable Development Goals (SDGs) target of reducing the under five mortality rate to as low as 12 deaths per 1,000 live births by 2030. The literature suggests that increase in government’s budgetary allocation to the health sector can improve country’s health outcomes. Evidence on the impact of health expenditures on health outcomes is mixed and limited in developing countries. This study aims to analyze the impact of public health expenditures on health outcomes, among other control variables in Kenya. The study uses time series data from 1970 to 2018. The variables are found to be integrated of different orders suggesting the choice of Autoregressive Distributed Lag (ARDL) model. ARDL provides a useful link between long run equilibrium relationships and short run disequilibrium dynamics is estimated. The ARDL bounds test suggests presence of cointegration thus leading to the estimation of Error Correction Model (ECM). The findings suggest that improvements in public health expenditures enhance health outcomes in Kenya. The control variablesthat are found to be important determinants of infant mortality rate in Kenya include the national income and number of hospital beds per 100, 000. The study recommends that Kenyan government should increase annual budgetary allocation to health sector. Such increase is likely to lead to investments in physical and human capital in the health sector thus translating to improved health outcomes in Kenya.